Efficacy of oral nystatin treatment for patients with oral mucosal dysesthesia but without objective oral mucosal manifestations and necessity of Candida culture test before oral nystatin treatment - Ding-Shan Peng; Chih-Hui Lo; Yu-Lun Tseng; Shun Li Kuo; Chun-Pin Chiang; Meng-Ling Chiang (Elsevier, 2022)
Background/purpose: Previous studies have shown that some of the patients with oral mucosal dysesthesia but without objective oral mucosal manifestations (so-called oral dysesthesia patients in this study) may have good responses to oral nystatin treatment. This study evaluated the efficacy of oral nystatin treatment for oral dysesthesia patients and the necessity of Candida culture test before oral nystatin treatment. Materials and methods: The 147 oral dysesthesia patients were divided into 3 groups: Candida culture (+) group (n = 29), Candida culture (−) group (n = 34), and without Candida culture test group (n = 84), and treated with oral nystatin. The pain improvement was evaluated by the reduction of numeric pain rating scale (NRS) and global perceived effects (GPE). We defined the GPE score ≥4 points as a great improvement. Results: We found that 44.8% of 29 patients in the Candida culture (+) group, 47.1% of 34 patients in the Candida culture (−) group, and 47.6% of 84 patients in the without Candida culture test group showed a significant reduction in the NRS score and achieved a great improvement after oral nystatin treatment for 1-4 weeks. Moreover, 72.4% of our 29 patients with Candida culture test achieved a great improvement within one week, and all the 29 patients achieved a great improvement within 4 weeks of oral nystatin treatment. Conclusion: A portion of our oral dysesthesia patients are infected by Candida and it is beneficial to our patients to use oral nystatin treatment before the Candida culture test.